Investigation of mobile devices usage and mobile augmented reality applications among older people - Abd Malik, Sofianiza; Abdullah, Lili Marziana; Mahmud, Murni; Azuddin, Muna (2014)
M￼￼￼￼obile devices such as tablets and smartphones have allow users to communicate, entertainment, access information and perform productivity. However, older people are having issues to utilise mobile devices that may affect their quality of life and wellbeing. There are some potentials of mobile Augmented Reality (AR) applications to increase older users mobile usage by enhancing their experience and learning. The study aims to investigate mobile devices potential barriers and influence factors in using mobile devices. It also seeks to understand older people issues in using AR applications.